Changes in the vocal parameters of teachers during the school year - Vera García, Verónica; Merino Gálvez, Esteban; Prieto Merino, David; Carazo Díaz, Carmen (Revista de Investigación en Logopedia, 2022)
The voice is a fundamental tool for the teacher. The alteration of its basic qualities is defined as dysphonia and it turns out to be very common. Our objective is to study whether the voice of teachers changes, as a consequence of the vocal effort caused by their profession, between the three school terms in a year and within a working day, measuring the acoustic voice quality index (AVQI). In addition, we study whether the change within the working day differs across the school terms. The sample include 93 teachers of which 40 teach in a public center and 53 in a subsidized center, 29% are men and 71% are women, 41.4% teach in primary education and 58.6% in secondary education. The PRAAT acoustic analysis program was used for voice recording. There is evidence that in the second and third terms the AVQI parameter worsens in teachers significantly after their school day and more markedly in those who teach secondary education. Teachers in public schools register AVQI levels significantly higher than those in subsidized schools. Dysphonia is significantly lower in teachers who teach the subjects of music, a foreign language and / or physical education. No significant AVQI changes are found between the different school terms.
Keywords: Dysphony; Educational centers; PRAAT; Vocal Quality Acoustic Index; Vocal Quality